Pembrolizumab in Vaginal Carcinoma: A Case Report and Review of the Literature - Maria Giuseppa Vitale; Cecilia Nasso; Beatrice Riccò; Alessandro Bocconi; Chiara Chiavelli; Cinzia Baldessari; Stefania Pipitone; Francesca Bacchelli; Laura Botticelli; Massimo Dominici; Roberto Sabbatini (Case Reports in Oncology, 2024)
Introduction: Vaginal cancer is a rare gynecologic malignancy. While in a localized disease, concurrent chemoradiation grants local control and better overall survival, in a metastatic setting, the management options are very limited. Furthermore, recurrent cervical, vulvar, and vaginal carcinomas notoriously develop resistance to treatment, and consequently, their prognosis is still poor. Case Presentation: We herein present the case of a woman with a nodal relapse of vaginal carcinoma, effectively treated with third-line immunotherapy. We will also provide a review of the literature on the new therapeutic strategies for advanced vaginal carcinoma, with a focus on pembrolizumab immunotherapy. Conclusion: Pembrolizumab might represent a promising option for the management of vaginal and vulvar cancer, but data to support its use in this setting are still lacking. This case highlights the need for further investigation and trial designs for this rare disease.